2011
DOI: 10.1038/ijo.2011.37
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Children's Eating Habits Questionnaire used in the IDEFICS study by relating urinary calcium and potassium to milk consumption frequencies among European children

Abstract: Background: Measuring dietary intake in children is notoriously difficult. Therefore, it is crucial to evaluate the performance of dietary intake assessment methods in children. Given the important contribution of milk consumption to calcium (Ca) and potassium (K) intakes, urinary calcium (UCa) and potassium (UK) excretions in spot urine samples could be used for estimating correlations with milk consumption frequencies. Objective: The aim of this study was to evaluate the assessment of milk consumption freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 40 publications
0
85
1
Order By: Relevance
“…Three studies reported using a 7 d weighed food record (21,23,28) and five studies reported using an estimated food record of 3 to 7 d (16,17,25,29) , one of which was web-based (29) . Three studies used a single 24 h recall (12,13,20) and four (18,19,27,30) (14) .…”
Section: Tool Propertiesmentioning
confidence: 99%
“…Three studies reported using a 7 d weighed food record (21,23,28) and five studies reported using an estimated food record of 3 to 7 d (16,17,25,29) , one of which was web-based (29) . Three studies used a single 24 h recall (12,13,20) and four (18,19,27,30) (14) .…”
Section: Tool Propertiesmentioning
confidence: 99%
“…10 The final CEHQ-FFQ asked for the consumption frequency of 43 pan-European food items of 14 food groups. 11 It was used in the whole sample of the IDEFICS baseline examination from September 2007 to May 2008 and was completed for more than 15 000 children between 2 and 9 years of age from the eight survey centres.…”
Section: Methodsmentioning
confidence: 99%
“…31,32 Food consumption assessed by the CEHQ was validated against selected nutrients measured in blood and urine samples. 33 The new method to analyse the fatty acid profile in a dried drop of blood was compared with the standard analysis of serum and erythrocytes from venous blood. A validation study was carried out to compare uniaxial and triaxial accelerometers in children and to validate them using doubly labelled water as the gold standard, and to also validate body composition measures using three-and fourcompartment models.…”
Section: Quality Managementmentioning
confidence: 99%